The Benefits of Near-field Manipulation and Viewing to Distant Object Manipulation in VR - Babu, Sabarish V.; Hsieh, Wei-An; Chuang, Jung-Hong (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2024)
In this contribution, we propose to enhance two distant object manipulation techniques, BMSR (Bimanual Near-Field Metaphor with Scaled Replica) and the classic Scaled HOMER (Scaled Hand-Centered Object Manipulation Extending Ray Casting), via nearfield scaled replica manipulation and viewing. In the proposed Direct BMSR, context replicas are displayed so that the target replica can be manipulated relative to its context, allowing the user to directly manipulate the target replica in their arm's reach space. Some additional features were implemented to make Direct BMSR an effective interface for manipulating objects from a distance. We proposed Scaled HOMER+NFSRV, which augments Scaled HOMER with a near-field scaled replica view (NFSRV) of the target object and its context, enabling the user to observe how the target replica is manipulated in relation to its context in their arm's reach space while manipulating it from a distance. We conducted a between-subjects empirical evaluation of BMSR, Direct BMSR, Scaled HOMER, and Scaled HOMER+NFSRV. Our findings revealed that Direct BMSR and Scaled HOMER+NFSRV significantly outperformed BMSR and Scaled HOMER, respectively, in terms of accuracy. This finding highlights the advantages of adding near-field scaled replica viewing and manipulation with respect to distant object manipulation.